2008
DOI: 10.5465/amr.2008.27749365
|View full text |Cite
|
Sign up to set email alerts
|

Positive Social Interactions and the Human Body at Work: Linking Organizations and Physiology

Abstract: Human physiological systems are highly responsive to positive social interactions, but the organizational importance of this finding largely has been unexplored. After reviewing extant research, we illustrate how consideration of the physiology of positive social interactions at work opens new research questions about how positive social interactions affect human capacity and how organizational contexts affect employee health and physiological resourcefulness. We also address the practical implications of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
345
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(397 citation statements)
references
References 131 publications
(66 reference statements)
15
345
0
5
Order By: Relevance
“…For example, they should resist short-term production pressures which are often met at the cost of compromising subordinates' safety (Pate-Cornell, 1990). Eventually, leaders will create safer work conditions for subordinates, as demonstrated in previous studies in which high quality of social relationship was found to promote safety (Geller, 1991) and health (Heaphy and Dutton, 2008).…”
Section: Trust In the Leader And Safetymentioning
confidence: 79%
“…For example, they should resist short-term production pressures which are often met at the cost of compromising subordinates' safety (Pate-Cornell, 1990). Eventually, leaders will create safer work conditions for subordinates, as demonstrated in previous studies in which high quality of social relationship was found to promote safety (Geller, 1991) and health (Heaphy and Dutton, 2008).…”
Section: Trust In the Leader And Safetymentioning
confidence: 79%
“…These social resources are endogenously produced through supportive interactions between an individual and others (e.g., their supervisors), and emerge in the organizational climate through repeated exposure to such interactions (Feldman, 2004;Worline et al, 2002). These resources are associated with physiological changes that lead to physical strength and health (Heaphy & Dutton, 2008;Reis & Gable, 2003). Thus, positive interpersonal relationships with managers at work are likely to enable employees to feel and display authentic positive emotions in the service interaction, and to limit their display of hostile emotions.…”
Section: Lmx Quality and Employees' Displays Of Hostilitymentioning
confidence: 98%
“…Keep in mind scholars' findings from domestic and foreign, we can mainly summarized the impact of workplace ostracism from three aspects: 1) workplace ostracism could affect mental health of members in the organization [6], and reduce their satisfaction; 2) the ostracism would reduce workplace citizenship behavior and then lead to counter-productive behavior; 3) workplace ostracism is also an influential variable used to explain why employees made poor performance [7].…”
Section: Research On the Effects Of Workplace Ostracismmentioning
confidence: 99%
“…When an employee faced workplace ostracism, emotions with others would break out. In order to increase emotional resources and maintain physical and mental health, people needed social contact to share their feelings or thoughts [6]. When the needs sharing emotion could not be satisfied, emotional resources were missing and led to emotional exhaustion [11].…”
Section: Workplace Ostracism and Employee Psychologymentioning
confidence: 99%